Bond markets in Malaysia & Singapore - Ariff, Mohamed; Cheng, Fan Fah; Heng, Neoh Vee (Universiti Putra Malaysia Press, 2008)
This book is about two bond markets respectively in Malaysia and Singapore. The book describes the historical development of these markets, and provides for the first time, both operational details about how the markets operate, as well as identifying the economic and financial behaviour of the markets. Necessarily, references to theories of how the market ought to behave and how they actually behave are documented for these price-efficient bond instruments.